ARCO Consensus on the Pathogenesis of Non-traumatic Osteonecrosis of the Femoral Head - Cui, Quanjun (J Korean Med Sci, 2021)
Osteonecrosis of the femoral head (ONFH) is a devastating disease frequently leading to femoral head collapse and hip arthritis. Specifically, non-traumatic ONFH primarily affects young and middle-aged adults. Although compromised local circulation of the femoral head seems to be pathognomonic for the disease, the pathogenesis is perplexing and continues to be an area of scrutiny and research. Comprehension of the pathogenesis is of crucial importance for developing and guiding treatments for the disease. Therefore, we provide an up-to-date consensus on the pathogenesis of non-traumatic ONFH.